Step
*
1
2
1
1
of Lemma
rlog-rmul
1. x : ℝ
2. r0 < x
3. y : ℝ
4. r0 < y
5. r0 < (x * y)
6. λx.(rlog(x * y) - rlog(y)) ∈ (r0, ∞) ⟶ℝ
7. c : ℝ
8. ∀x:{x:ℝ| x ∈ (r0, ∞)} . (rlog(x) = ((rlog(x * y) - rlog(y)) + c))
9. rlog(r1) = ((rlog(r1 * y) - rlog(y)) + c)
10. rlog(x) = ((rlog(x * y) - rlog(y)) + c)
⊢ rlog(x * y) = (rlog(x) + rlog(y))
BY
{ ((Assert r0 < (r1 * y) BY (nRNorm 0 THEN Auto)) THEN (nRNorm (-3) THENA Auto) THEN (RWO "rlog1" (-3) THENA Auto)) }
1
1. x : ℝ
2. r0 < x
3. y : ℝ
4. r0 < y
5. r0 < (x * y)
6. λx.(rlog(x * y) - rlog(y)) ∈ (r0, ∞) ⟶ℝ
7. c : ℝ
8. ∀x:{x:ℝ| x ∈ (r0, ∞)} . (rlog(x) = ((rlog(x * y) - rlog(y)) + c))
9. r0 = c
10. rlog(x) = ((rlog(x * y) - rlog(y)) + c)
11. r0 < (r1 * y)
⊢ rlog(x * y) = (rlog(x) + rlog(y))
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  r0  <  x
3.  y  :  \mBbbR{}
4.  r0  <  y
5.  r0  <  (x  *  y)
6.  \mlambda{}x.(rlog(x  *  y)  -  rlog(y))  \mmember{}  (r0,  \minfty{})  {}\mrightarrow{}\mBbbR{}
7.  c  :  \mBbbR{}
8.  \mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  (r0,  \minfty{})\}  .  (rlog(x)  =  ((rlog(x  *  y)  -  rlog(y))  +  c))
9.  rlog(r1)  =  ((rlog(r1  *  y)  -  rlog(y))  +  c)
10.  rlog(x)  =  ((rlog(x  *  y)  -  rlog(y))  +  c)
\mvdash{}  rlog(x  *  y)  =  (rlog(x)  +  rlog(y))
By
Latex:
((Assert  r0  <  (r1  *  y)  BY
                (nRNorm  0  THEN  Auto))
  THEN  (nRNorm  (-3)  THENA  Auto)
  THEN  (RWO  "rlog1"  (-3)  THENA  Auto))
Home
Index